2023
DOI: 10.14245/ns.2346494.247
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Skeletal Muscle Mass, Lumbar Lordosis, and Chronic Low Back Pain in the Elderly

Myung Woo Park,
Sang Jun Park,
Sun Gun Chung

Abstract: Objective: Loss of skeletal muscle mass is known to be associated with multiple morbidities. However, there is a dearth of reports on its association with lumbar lordosis and musculoskeletal pain. The aim of this study was to delineate the cross-sectional relationship between loss of skeletal muscle mass, lumbar lordosis, and chronic low back pain (CLBP).Methods: A total of 721 medical records were reviewed, and data from 165 older subjects (over 65 years old; 81 men and 84 women) were retrospectively analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In various LBP animal models, Wang et al (2021) also found lower abundance of Lachnospiraceae NK4A136 group in rats with lumbar disk herniation compared to the control group. A cross-sectional study revealed a significant reduction in skeletal muscle mass index in patients with LBP compared to normal individuals ( Park et al, 2023 ). Sugimura et al (2022) found a positive relationship between the abundance of Eisenbergiella and skeletal muscle mass, suggesting a reasonable hypothesis that Eisenbergiella may prevent LBP by increasing lumbar skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…In various LBP animal models, Wang et al (2021) also found lower abundance of Lachnospiraceae NK4A136 group in rats with lumbar disk herniation compared to the control group. A cross-sectional study revealed a significant reduction in skeletal muscle mass index in patients with LBP compared to normal individuals ( Park et al, 2023 ). Sugimura et al (2022) found a positive relationship between the abundance of Eisenbergiella and skeletal muscle mass, suggesting a reasonable hypothesis that Eisenbergiella may prevent LBP by increasing lumbar skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread prevalence of cervical muscle degeneration, it has not garnered commensurate attention relative to the lumbar spine ( 40 44 ). He et al.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread prevalence of cervical muscle degeneration, it has not garnered commensurate attention relative to the lumbar spine (40)(41)(42)(43)(44). He et al observed a degeneration rate of 69.1% in the paraspinal muscles (Goutallier Grade ≥1.5) among patients with two-level cervical disc degenerative disease (24).…”
Section: Discussionmentioning
confidence: 99%